THE GEOLOGY OF ALUMINUM PHOSPHATE AND SULPHATES OF THE ALUNITE GROUP MINERALS: A REVIEW - Dill H.G. (My University, 2001)
Aluminium phosphates and sulphates of the alunite supergroup (APS minerals) occur in a wide range of environments of formation covering the metamorphic, igneous and sedimentary realms. Supergene processes, including mineral dressing and dumping when sulphide ores are mined, as well as hypogene alteration are also responsible for the precipitation of APS minerals. In these environments, complex solid solution series (s.s.s.) can form. The general formula of these alunite minerals is AB3 (XO4)2(OH)6, where A is a large cation (Na, U, K, Ag, NH4, Pb, Ca, Ba, Sr, REE). B sites are occupied by cations of the elements Al, Fe, Cu and Zn. In nature, the anion (XO4)x− is dominated by P and S. Mineral dressing and identification of APS minerals often needs a combination of highly sophisticated measures including Atterberg settling methods, XRD, DTA, TGA, TEM-EDX, SEM, EMPA and XRF.